The measurement of the dipole anisotropy of protons and helium cosmic rays with the PAMELA experiment. Issue 3 (January 2016) - Karelin, A V; Adriani, O; Barbarino, G C; Bazilevskaya, G A; Bellotti, R; Boezio, M; Bogomolov, E A; Bongi, M; Bonvicini, V; Bottai, S; Bruno, A; Cafagna, F; et al.
Abstract: In the framework of the PAMELA experiment the features of the large-scale anisotropy have been measured within the energy range 1-20 TeV/n. The measurements were carried out with the use of the calorimeter on the base of the hypothesis about the existence of a dipole anisotropy. The amplitude and phase of the dipole were obtained. The results are in agreement with the ground-based observations.